Somatosensory Temporal Discrimination in Autism Spectrum Disorder. Issue 4 (1st February 2021) - Buyuktaskin, Dicle; Iseri, Elvan; Guney, Esra; Gunendi, Zafer; Cengiz, Bulent
Abstract : Sensory differences are common in Autism Spectrum Disorder (ASD). While there is no well‐accepted method to measure sensory differences objectively, there is accumulating evidence from recent years concerning sensory perception, including data concerning temporal discrimination thresholds of individuals with ASD as measured by different measures. The somatosensory temporal discrimination (STD) test measures the threshold at which an individual can temporally discriminate multiple tactile stimuli delivered in succession. We aimed to investigate tactile perception in ASD and hypothesized that children with ASD have impaired STD related to their subjective sensory symptoms and daily difficulties. Thirty adolescents with ASD and 30 typically developed subjects were recruited. The Childhood Autism Rating Scale, Strengths and Difficulties Questionnaire, and Adolescent/Adult Sensory Profile were implemented before STD evaluation. Average somatosensory detection (1.48 ± 0.42) and discrimination thresholds (112.70 ± 43.45) of the children with ASD were significantly higher ( P = 0.010, P = 0.001, respectively) than those of the controls (1.18 ± 0.42, 79.95 ± 31.60, respectively). Sensory seeking scores of the ASD group (40.8 ± 7.60) were significantly lower ( P = 0.024) than those of the control group (45.83 ± 9.17). However, the psychophsycal thresholds did not have any statistically significant relationships with subjective sensory symptoms or daily difficulties. This study demonstrates impaired sensory processing in ASD evaluated by STD and its lack of relationship with subjective sensory symptoms and daily difficulties. This psychophysical evidence of increased STD thresholds and decreased sensory seeking profile supports the disturbances in the regulation of sensory processing in ASD. Lay Summary: Sensory differences are common in autism; however, there is no well‐accepted method to measure them objectively. This study aims to investigate somatosensory differences and their relation with sensory and emotional/behavioral difficulties of children with autism. We show that autistic children have higher tactile discrimination thresholds and fewer sensory seeking behaviors. This supports the presence of impairments in sensory processing in autism. Measuring the sensory differences may help understanding clinical symptoms and neurobiological underpinings of autism. Autism Res 2021, 14: 656–667 . © 2021 International Society for Autism Research and Wiley Periodicals LLC